(untitled) (Jurnal Kemanusiaan, 2017)
The higher education sector in Malaysia is experiencing stiff competition. Both public and private higher education institutions (HEIs) are required to teach, educate as well as to survive economically. Thus, the ability to attract students, either local or foreign, has become a crucial advantage. However, research looking into foreign students’ perceptions on graduate school selection is still very lacking in the local setting. Thus, this study aims to identify the factors that influence the foreign undergraduates’ intention to study at graduate school and to verify their relationships. The results indicated that location, low cost, university reputations, academic programs, learning facilities and country image were having significant relationships with foreign undergraduates’ intention to study at graduate school. However, family/peers influence was the only factor that did not have any significant relationship. HEI operators are therefore recommended to focus on the previous six factors, but should pay less attention to the latter. Recommendations for future research have also been put forth in this paper.